Effect of metal adatoms on hydrogen adsorption properties of phosphorene. (21st April 2017) - Yu, Zhiyuan; Lei, Shuangying; Wan, Neng; Luan, Shan; Shen, Haiyun; Yu, Hong
Abstract: Based on first-principles density functional theory, we have investigated hydrogen storage on metal adatoms decorated phosphorene. Almost all metals including alkali, alkaline, 3d, 4d and 5d transition metals (TM) as well as post-TMs are considered to decorate phosphorene, and most metals exhibit an enhancement of H2 adsorption energy ( E a ), except for Zn, Cd, Hg, and all post-TMs. Nine metals show ideal Ea within the energy window 0.2–0.6 eV/H2 for practical application purposes. Among them, Li, Sc, Ti, Y, Zr, and La exhibit superior adsorption abilities of 3–5 H2 per adatom. Based on local density of states and Barder analyses, underlying mechanisms of interaction between phosphorene, metal, and H2 are also discussed.